Field notes contributed by Darwin Koenig, spring 1984 - Koenig, Darwinet al (1984)
Field notes were contributed by Darwin Koenig, spring 1984. He observed 18 bird species, including Cattle Egrets and a Peregrine Falcon in New Albin. He observed Rusty Blackbirds with Joseph P. Schaufenbuel in New Albin. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed